2020
DOI: 10.20452/pamw.15546
|View full text |Cite
|
Sign up to set email alerts
|

Factors determining elective cardioversion preceded with transesophageal echocardiography: two cardiology centres’ experiences

Abstract: INTROduCTION Although guidelines endorse cardioversion after adequate non-vitamin K antagonist oral anticoagulant (NOAC) treatment without prior transesophageal echocardiography (TEE), the majority of patients still undergo this examination. ObjECTIvEs The aim of this study was to assess factors determining the decision to perform TEE in patients with atrial fibrillation (AF) who are eligible for elective cardioversion. PATIENTs ANd mEThOds In this study, we evaluated the medical records of consecutive patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…While it offers the ability to directly visualize thrombi in the LAA, the actual utility of routine use before cardioversion to prevent thromboembolism in AFib patients who have undergone adequate anticoagulation is still evolving [ 23 ]. Despite recommendations against TEE in adequately anticoagulated patients, in practice many clinicians choose to evaluate patients with TEE regardless of anticoagulation status when they have an increased risk of thromboembolism [ 24 ].…”
Section: Reviewmentioning
confidence: 99%
“…While it offers the ability to directly visualize thrombi in the LAA, the actual utility of routine use before cardioversion to prevent thromboembolism in AFib patients who have undergone adequate anticoagulation is still evolving [ 23 ]. Despite recommendations against TEE in adequately anticoagulated patients, in practice many clinicians choose to evaluate patients with TEE regardless of anticoagulation status when they have an increased risk of thromboembolism [ 24 ].…”
Section: Reviewmentioning
confidence: 99%
“…The results of the study by Frederiksen et al [ 11 ] involving a group of 2150 patients undergoing ECV were consistent with the results of the previous study. Thromboembolic complications were not observed in any of the patients during the 30-day follow-up period of this study, which included 668 patients treated with NOACs before ECV [ 12 ]. Also, Barysiene et al [ 13 ] did not acknowledge thromboembolic events in the 30-day follow-up period for a group of 432 patients receiving pertinent anticoagulant therapy prior to ECV.…”
Section: Thromboembolic Risk In the Peri-cardioversion Periodmentioning
confidence: 99%
“…An additional 4.6% of the centers recommended TEE routinely for all patients [ 41 ]. In the study including 668 AF patients treated with NOACs before ECV, TEE was performed in 54% of patients [ 12 ]. Data from the Outcomes Registry for Better Informed Treatment of Atrial Fibrillation II showed that 25% of patients had pre-cardioversion TEE [ 10 ].…”
Section: Tee Before Ecv In Clinical Practicementioning
confidence: 99%
“…The gold standard for the exclusion of LAAT is transesophageal echocardiography (TOE) [9,10]. However, there are no unequivocal data on whether patients awaiting ablation or electric cardioversion should routinely undergo TOE, which is an invasive procedure that should be performed by trained and experienced personnel [11][12][13][14]. Risk stratification according to sex is common in clinical practice.…”
Section: Introductionmentioning
confidence: 99%